Iron responsive elements mRNA regulate Alzheimer’s amyloid precursor protein translation through iron sensing - Khan, Mateen A. (Frontiers in Aging Neuroscience, 2025)
Iron responsive element (IREs) mRNA and iron regulatory proteins (IRPs) regulate iron homeostasis. 5′-untranslated region motifs of APP IREs fold into RNA stem loops bind to IRP to control translation. Through the 5’-UTR APP IREs, iron overload accelerated the translation of the Alzheimer’s amyloid precursor protein (APP). The protein synthesis activator eIF4F and the protein synthesis repressor IRP1 are the two types of proteins that IREs bind. Iron regulates the competitive binding of eIF4F and IRP1 to IRE. Iron causes the IRE and eIF4F to associate with one other, causing the dissociation of IRPs and altered translation. In order to control IRE-modulated expression of APP, messenger RNAs are becoming attractive targets for the development of small molecule therapeutics. Many mRNA interference strategies target the 2-D RNA structure, but messenger RNAs like rRNAs and tRNAs can fold into complicated, three-dimensional structures that add another level of complexity. IREs family is one of the few known 3-D mRNA regulatory elements. In this review, I present IREs structural and functional characteristics. For iron metabolism, the mRNAs encoding the proteins are controlled by this family of similar base sequences. Iron has a similar way of controlling the expression of Alzheimer’s APP as ferritin IRE RNA in their 5ÚTR. Further, iron mis regulation by IRPs can be investigated and contrasted using measurements of expression levels of APP, amyloid-β and tau formation. Accordingly, IRE-modulated APP expression in Alzheimer’s disease has great therapeutic potential through targeting mRNA structures.